Coping and resilience in riverine Bangladesh. (1st January 2020) - Sultana, Parvin; Thompson, Paul M.; Wesselink, Anna
ABSTRACT: This paper investigates the impacts of two successive years of severe floods on households, their coping strategies and resilience to riverine hazards in northern Bangladesh. Based on focus groups and interviews with the same households after floods in 2016 and 2017, we found a cumulative decline in assets through sale of livestock and borrowing, and almost all households evacuated short term to higher places. Three notable recent ways that vulnerable households use socio-hydrological landscapes to enhance their resilience to hazards were revealed. Firstly, local flood protection embankments were the main destination for evacuation and were highly valued as safe places, although they breached and failed to protect the land. Secondly, community organisations, formed mainly for livelihood enhancement, took initiatives to provide warnings, to help households relocate during floods, and to access relief and rehabilitation services. Thirdly, seasonal migration by men, particularly to urban areas, is an important element of long-term coping and resilience based on diversified livelihoods for about 70% of these rural households. Although the unintended use of infrastructure, social capital and urban opportunities all form part of coping and resilience strategies in hazardous riverine landscapes, the high mobility that they are based on is not supported by enabling policies.